Health-Related Physical Fitness and Quality of Life in Children and Adolescents With Isolated Left-to-Right Shunt - Fuertes Moure, Angeles; Meyer, Michael; Häcker, Anna-Luisa; Reiner, Barbara; Brudy, Leon; Oberhoffer, Renate; Ewert, Peter; Müller, Jan (Frontiers in Pediatrics, 2019)
Objective: Atrial (ASD) and ventricular septal defects (VSD) represent the most common congenital heart defects (CHD) and are considered simple and curable. This study investigates long-term functional outcomes in children with such defects. Patients and Methods: We examined 147 patients (74 girls, 12.1 ± 3.5 years) with isolated shunts (ASD: 54%, VSD: 46%) for their Health-Related Physical Fitness (HRPF) and Health-Related Quality of Life (HRQoL). Native condition was present in 58 patients, interventional closure of the defect was performed in 42 and surgical closure in 47. For comparison, a healthy control group (CG) of 1724 children (48.9% girls, 12.8 ± 2.8 years) was recruited within two recent school projects. Results: After adjustment for age and sex, children with ASD and VSD presented lower HRPF (z-score healthy peers: 0.02 ± 0.73, ASD: -0.41 ± 0.73, p<.001; VSD: -0.61 ± 0.73, p<.001) then healthy peers. Transferred into percentiles, VSD were on the 26th and ASD on the 34th percentile of the healthy peers. HRQoL did not differ between peers and CHD with isolated shunts (healthy peers: 76.1 ± 9.7, ASD: 76.2 ± 9.9, p=.999; VSD: 78.7 ± 9.7, p=.316). Regarding the surgical history of the shunts (native, percutaneously treated, surgically treated), there were also no difference in-between these three states, nor differed HRPF and HRQoL in-between gender. Conclusions: Children with ASD or VSD have impaired HRPF but normal HRQoL. Early childhood sports promotion could be a good measure to counteract these restrictions in HRPF at an early stage.